2019
DOI: 10.1111/bjet.12751
|View full text |Cite
|
Sign up to set email alerts
|

Exploring primary school teachers’ technological pedagogical content knowledge (TPACK) in online collaborative discourse: An epistemic network analysis

Abstract: The contextual influences on technological pedagogical content knowledge (TPACK) enactment and the method of TPACK assessment remain to be important research topics. Discourse data of 81 teachers in an online professional learning community were collected and analyzed based on the framework of TPACK. Frequency distribution and time series characteristics of teachers’ knowledge domains were analyzed. In addition, epistemic network analysis was used to compare the epistemic network characteristics of teachers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 43 publications
2
47
2
2
Order By: Relevance
“…Similar results were found by Roig-Vila, Mengual-Andres, and Quinto-Medrano (2015). In addition, Zhang, Liu, and Cai (2019) found that elementary teachers had lower TPACK levels compared with middle school teachers' TPACK levels. According to the researchers, this difference may be related to teachers' academic performances and professional development performances in teacher education programs.…”
Section: Conclusion Discussion and Suggestions Regarding Technological Knowledgesupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results were found by Roig-Vila, Mengual-Andres, and Quinto-Medrano (2015). In addition, Zhang, Liu, and Cai (2019) found that elementary teachers had lower TPACK levels compared with middle school teachers' TPACK levels. According to the researchers, this difference may be related to teachers' academic performances and professional development performances in teacher education programs.…”
Section: Conclusion Discussion and Suggestions Regarding Technological Knowledgesupporting
confidence: 79%
“…Avcı and Ateş (2018) also put strong emphasis on professional development programs to increase teachers' active and effective usage of technology and as a result, increase their TPACK levels. Zhang, Liu, and Cai (2019) stated that elementary teachers rarely use technology in their lessons, especially at lower grades, and they prefer to use storytelling and children's songs in their instruction. In their study, Topçu and Masal (2020) examined mathematics teachers' perceptions and self-evaluation skills about TPACK by considering how and to what extent they use technology in their instruction and found that teachers had the highest score for the PCK sub-dimension and the lowest score for the TK sub-dimension.…”
Section: Conclusion Discussion and Suggestions Regarding Technological Knowledgementioning
confidence: 99%
“…TPACK also becomes the focus of a variety of studies. In a study conducted in China by Zhang, Liu, and Cai (2019) on primary school teachers, the results indicated that the teachers engaged in more extensive group collaborations had a rich, organized and flexible knowledge structure of TPACK. In terms of age effects, that study found that younger teachers turned out to be better in terms of pedagogical knowledge and pedagogical content knowledge, while more experienced teachers scored higher in terms of technological knowledge and pedagogical knowledge.…”
Section: The Significance Of the Studymentioning
confidence: 99%
“…It will be sustainable education, if teachers ready to change their mindset and teaching role by non-focused theory. Classroom environments should challenge students in the way of creatively learning and solvable problem classroom through integration [27], and teachers have to pay their lesson design by incorporating pedagogy to fit with content or pedagogical content knowledge [28][29][30]. However, technology may be referred to communication and tools for creating which need to be discussed by different school practices.…”
Section: Discussionmentioning
confidence: 99%